IMPLIKATUR PERCAKAPAN DALAM VIDEO ANIMASI HASAN IBN HAYTHAM (KAJIAN PRAGMATIK) - Hamas, Marisa Salsabila (Hijai - Journal on Arabic Language and Literature, 2021)
ABSTRACTWe often encounter linguistic phenomena in various kinds of conversational models, but not all conversations can be directly understood because they contain hidden meanings with certain goals from both the speaker and the partner. This study aims to describe the meaning of conversations containing conversational implicatures and identify the types of conversational implicatures in Hasan Ibn Haytham's animated videos from episodes 1-3. This type of research is descriptive qualitative. Sources of data in the form of primary and secondary data sources. Data collection is done by watching and taking notes. The data analysis method was carried out by means of data reduction, data presentation, and drawing conclusions. Researchers used persistence, data triangulation, and discussion to test the validity of the data. The results of this study are the researchers found 12 utterances containing conversational implicatures with the intention of showing information of pleasure, sadness, stating something, amazement, pride in themselves, annoyance, petition and rejection. There are 3 types of implicatures, namely special conversational implicatures, conventional conversational implicatures, and scale conversational implicatures. ABSTRAKFenomena kebahasan sering kita jumpai dalam berbagai macam model percakapan, namun tidak semua percakapan dapat langsung difahami karena mengandung makna tersembunyi dengan adanya tujuan tertentu baik dari penutur maupun mitra tutur. Penelitian ini bertujuan untuk mendeskripsikan makna percakapan yang mengandung implikatur percakapan dan mengidentifikasikan jenis implikatur percakapan dalam video animasi Hasan Ibn Haytham dari episode 1-3. Jenis penelitian ini adalah deskriptif kualitatif. Sumber data berupa sumber data primer dan sekunder. Pengumpulan data dilakukan dengan teknik tonton dan catat. Metode analisis data dilakukan dengan cara reduksi data, penyajian data, dan penarikan kesimpulan. Peneliti menggunakan ketekunan, triangulasi data, dan berdiskusi untuk menguji keabsahan data. Hasil dari penelitian ini adalah peneliti menemukan 12 tuturan yang mengandung implikatur percakapan dengan maksud menunjukkan informasi kesenangan, kesedihan, menyatakan suatu hal, ketakjuban, membanggakan diri sendiri, kekesalan, permohonan dan penolakan. 3 jenis implikatur, yakni implikatur percakapan khusus, konvensional, dan berskala.